Food safety and hygiene knowledge, attitudes and practices in street restaurants selling chicken in Ouagadougou, Burkina Faso - Gemeda, Biruk Alemu; Dione, Michel; Ilboudo, Guy; Assefa, Ayalew; Lallogo, Valerie; Grace, Delia; Knight-Jones, Theodore J. D. (Frontiers in Sustainable Food Systems, 2024)
Chicken is the most commonly consumed animal source food in street restaurants in Burkina Faso. In most of these restaurants, slaughtering, processing, and cooking practices are carried out under poor hygienic conditions. A cross-sectional survey using a semi-structured interview was carried out to assess food safety knowledge, attitude, and hygienic practices of food handlers in street restaurants selling chicken in Burkina Faso's capital, Ouagadougou. One hundred chicken restaurants were randomly selected, and food handlers were interviewed. Most restaurants served eat-in and takeaway chicken (66%); the remaining 34% were takeaway only; restaurants served grilled, flamed or roasted chicken. Only 11% of the food handlers had training on food hygiene and safety. Half the outlets were not regularly inspected by the authorities. Less than half (40%) slaughtered their own chickens at the restaurant: of these 85% bled chickens on bare earth. About 80% cleaned the bleeding surface immediately after slaughter with water but only 20% used water with either soap or disinfectantdetergent. Eighty-two percent of them used the same cloth during slaughtering and food preparation stages. Many used the same knife in all stages of the slaughtering process. Two-thirds kept carcasses unrefrigerated at ambient temperature until cooking started. Around a quarter buried slaughter waste on-site whereas 20% disposed of it on the street near the restaurant. Only 20% had taken steps to improve food safety, and about 80% of food handlers stated that cleanliness and hygiene were not important to their customers when choosing where to eat. Almost half (42%) the food handlers continued to work when they were ill. The poor standards of hygiene observed are typical for street food and small-scale eateries in LMICs in Sub Saharan Africa. An integrated approach is required to improve the situation, including staff training, introduction of food-grade equipment and appropriate technology, behavior-change approaches, as well as worker and consumer awareness campaigns on good food safety practices. However, significant, sustained improvement in food safety will also require major upgrading of infrastructure and facilities including power and water supply, and coldchain.